The effects of cyberbullying victimization on cyberbullying perpetration among Chinese college students: callous-unemotional traits and the moderating role of Internet morality - Zhang, Wenhai; Sha, Jingying (Frontiers in Psychology, 2024)
Introduction: The Internet has triggered a series of online deviant behaviors, and cyberbullying is one of them. Cyberbullying victimization as a category of frustration and the aggression triggered by it has been confirmed by many studies. Previous studies have explored the relationship between cyberbullying victimization and cyberbullying perpetration. However, the boundary conditions of the two have yet to be sufficiently explored, and this paper will further explore the moderating effect in the transformation mechanism. Methods: The convenience sampling method was used to select a cumulative total of 668 students from university students of several universities in Beijing for the study, using questionnaires including Cyberbullying Victimization Questionnaire, Cyberbullying Perpetration Questionnaire, The Callous-unemotional Traits Scale, and Internet Morality Questionnaire. Results: (1) Controlling for gender and grade, cyberbullying victimization has a positive relationship with cyberbullying perpetration. (2) Callous-unemotional traits moderated the relationship between cyberbullying victimization and perpetration. (3) Internet morality can moderate the relationship between cyberbullying victimization and perpetration. (4) Callous-unemotional traits and Internet morality can co-regulate the relationship between cyberbullying victimization and perpetration. Conclusion: The results indicate that cyberbullying victimization had a significant positive relationship with cyberbullying perpetration, a process moderated by callous-unemotional traits and Internet morality.